O POLSKIM PRAWIE UBEZPIECZEŃ GOSPODARCZYCH W KONTEKŚCIE WYMOGÓW ACQUIS COMMUNAUTAIRE UE (REASUMPCJA STANOWISK PREZENTOWANYCH W PRACACH IZBY) - Nowak, Stanisław (Zeszyty Prawnicze, 2017)
Po l i s h In s u r a n c e La w i n t h e C o n t e x t o f t h e ‘Ac q u i s Communautaire’ UE Requirements (Recapitulation of the Standpoints Presented in the Chamber’s Works) Summary Substantial changes of the legal status in the system of Polish economic insurance, called a revolution in the Polish insurance law, initiated by a series of bills dated 22 M ay 2003 and multiplicity of accompanying secondary legislation made the insurance market start numerous analytic works, also in the context o f the requirements to adapt to the com m unity law. These im portant and vast issues, already for some time, have been subject to studies and discussions taking place in the Insurance and Risk Management Cham ber of Commerce. They draw to a conclusion that the quality o f Polish law is unsatisfactory, the law is complicated and unclear. Further they show deficiencies in the knowledge of the com m unity law in Poland due to which a social and professional insurance education is necessary. Further adaptation measures should start from a substantial change of the law on insurance contract. This process should also regard the act insurance agencies. An urgent need of insurance education, belonging to a so-called Lisbon strategy adopted by the European Council in M arch 2000, is highly im portant for the insurance market.